Cashew Agroindustry Development Strategy in Wonogiri Regency: A Case Study on Nyamikan Kertohardjo SME - Khomah, Isti; Oktawidia, Ummala Azahra; Sutrisno, Joko (Journal Galung Tropika, 2025)
Nyamikan Kertohardjo is one of the SMEs producing cashew nuts in Wonogiri Regency. Small and Medium Enterprises (SMEs) or Small Medium Enterprise (SME) This company is facing obstacles in its development as one of the businesses in the largest cashew nut producing area. This research aims to determine the internal and external conditions of UKM Nyamikan Kertohardjo, design alternative strategies, and determine appropriate priority strategies for this UKM. This research uses a descriptive method with an analytical approach. Key informants are owners, employees, consumers, competitors and related local government offices taken using purposive sampling techniques. Research data was obtained from IFE, EFE, IE, SWOT, and QSPM analysis. The research results show that internal factors include human resources, management, finance, production, marketing and technology, while external factors include consumers, competitors, government, environment and economy. SWOT analysis produces 8 alternative strategies based on business position in quadrant IV. QSPM analysis produces a special strategy that can be implemented by Nyamikan Kertohardjo, namely maintaining and strengthening good relationships with consumers.